Milk Production in Integrated Systems: Review - Biavatti, H. A. Z.; Berber, G. C. M.; Berber, R. C. A. (Scientific Electronic Archives, 2014)
The pasture degradation and thermic stress are in economic trouble for milk producers. The use of silvopastoral system (SSP) is an important tool to minimize this loss, since it combines the production and conservation of natural resources, furthermore, provides the producer the potential to diversify the source of income of rural property, it is possible sale or own use of the products generated by the trees as timber, firewood and fruit. With the implementation of the SSP is possible to attenuate the effects of high temperatures caused by direct solar incidence on the animals, providing an ideal thermal comfort zone, resulting in increased production, it will expend less energy so that the animals are able to be as close as possible the necessary thermal comfort. Besides, with the adoption of this system, occurs a minor pasture degradation by promoting the formation of a microclimate favoring their establishment and maintenance, in addition to stabilizing soils, unpacked action of roots and preventing erosion. The purpose of this work was study the main aspects that affect the production of milk, proposing the use of integrated systems to minimize losses from thermal stress and degradation of pastures.